Strengthening Health Systems: A Comparative Analysis of Pakistan and Canada through the WHO Building - Mahapara; Nida Shoaib; Sameera Ali Rizvi; Syeda Tabeena Ali (Liaquat National Journal of Primary Care)
The Health System Building Blocks framework guided the holistic approach that has been promoted by the World Health Organization to strengthen the health systems. The framework is composed of six fundamental components: the health workforce, access to essential medicines, information systems, leadership/governance, and financing. These components have been strengthened along with challenges and strategies for indicators like HIV, Nutrition, Child health, and sanitation in Canada, a high-income country compared with a lower-middle-income country such as Pakistan. This commentary identifies certain health system challenges and opportunities for betterment in each country by evaluating the indicators inside the WHO Health System Building Blocks framework that has a health workforce, service delivery, health information systems, access to essential medicines, leadership/governance, and financing.